Computation of MHD flow of three-dimensional mixed convection non-Newtonian viscoelastic fluid with the physical aspect of gyrotactic microorganism - Ramzan, Muhammad; Shamshad, Usman; Rehman, Sadique; Saeed, Anwar; Kumam, Poom; Watthayu, Wiboonsak (Waves in random and complex media, 2025)
The present work is established for the examination of the MHD flow of three-dimensional mixed convection non-Newtonian viscoelastic nanofluid containing the gyrotactic microorganism toward the stretched sheet in a porous media. The Darcy-Forchheimer along with thermal radiation effects are evaluated. For the computation of the heat transmission mechanism, the theory of the Cattaneo-Christov heat flux in place of classical Fourier's law is used. The effect of the thermal relaxation time parameter over the boundary layer is predicted by using this theory of the Cattaneo-Christov heat flux problem. Further, the study of Brownian motion and thermophoretic influence are scrutinized. The problem formulation is formulated in the form of momentum equations in $ x - $ x - and $ y - $ y - directions, energy, mass and gyrotactic microorganism equations under the convective boundary condition. The analytical simulations of the current problem are performed by using the homotopic analysis scheme in a MATHEMATICA 12 software. The graphical investigation of the velocities in the directions of $ x - $ x - and $ y - $ y - axes, temperature, concentration and gyrotactic microorganism profiles of the nanofluid for numerous estimations of the distinct flow parameters are also elaborated. The physical aspect of the skin friction coefficients, Nusselt number, Sherwood number and density number of microorganisms are accomplished versus different flow parameters in a pictorial form. Some of the main results of the current problem are that intensifying estimations of the viscoelastic fluid parameter and magnetic field parameter increased the nanofluid velocity in $ x - $ x - direction. It is noted that the temperature of the nanoliquid is lesser for larger estimations of the Prandtl number and thermal relaxation time parameter. It is scrutinized that the Nusselt number of the nanoliquid is increased due to the increasing of radiation parameter.